New approaches for growth improvement in pejerrey Odontesthes bonariensis (Valenciennes, 1835) culture (Atherinomorpha: Atherinopsidae) - Solimano, Patricio J. (2015)
The pejerrey is the most important recreational species in shallow temperate lakes and reservoirs of Argentina and the attempts to develop its culture have started a century ago. A common constraint of pejerrey aquaculture is its poor growth under traditional intensive rearing techniques. The aim of this study was to evaluate the possibility to achieve and maintain high growth rates of pejerrey throughout the rearing process by semi-intensive culture method . Four floating cages were installed in La Salada de Monasterio Lake and each one was stocked with 300 juveniles (10.22 ±0.38cm; 6.52 ±0.82g). From January through March all fish were exposed to natural zooplankton as food source, whereas from April to September two cages were supplied daily with artificial food. The fish exposed to artificial supplementary diets exhibited significantly higher growth (17.5 ±0.98cm; 41.05 ±8.55g) than those in the control cages (15.02 ±0cm ; 23.5 ±0.84g), and exceeded the known values in pejerrey culture. The results suggest that the species potential growth is not fully achieved by common intensive methods and it can be improved by semi-intensive techniques. Accordingly a better understanding of the species nutritional requirements is needed to improve growth rates and enhance pejerrey culture.